Analisis Pengendalian Kualitas Produk Side Frame dan Bolster Terhadap Cacat Pengecoran Baja Menggunakan Metode Seven Tools di PT Barata Indonesia - Armadani, Moh Andrey Rifki; Putri, Erni Puspanantasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The steel casting industry plays an important role in supporting the transportation and infrastructure sectors; however, this process often encounters product defects that lead to decreased quality and increased rework costs. PT Barata Indonesia, as a manufacturer of railway components such as side frames and bolsters, still experiences a high defect rate averaging 23.16%, with cracks and porosity as the dominant defects. This study aims to analyze the quality control of steel casting products, specifically side frame and bolster components, using the Seven Tools of Quality Control as a means to identify and improve production defects. Data were obtained through field observations, interviews, and Quality Control reports from March to August 2025. The analysis utilized check sheets, Pareto charts, and fishbone diagrams to identify dominant defect types and their root causes. The results indicate that work methods, machine conditions, and material quality are the main causes. Recommendations focus on controlling pouring temperature, improving operator discipline, and conducting regular equipment maintenance.